2005
DOI: 10.4028/www.scientific.net/kem.293-294.591
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Failure in Multi-Bolt Composite Joints Using Finite Element Analysis and Bearing-Bypass Diagrams

Abstract: Abstract.A three-dimensional finite element model of a three-bolt, single-lap composite joint is constructed using the non-linear finite element code MSC.Marc. The model is validated against an experiment where the load distribution in the joint is measured using instrumented bolts. Two different joint configurations are examined, one with neat-fit clearances at each bolt-hole and another with a 240 µm clearance at one hole with neat-fits at the others. Bearing and by-pass stresses are extracted from the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…As the e/D ratio approaches 3.0, both parts of the specimen experience bearing failure, indicating the absence of tension failure (L1I). This result aligns with findings from prior investigations [ 69 , 70 , 71 , 72 , 73 , 74 ]. Alaattin Aktas reported that, while adjusting the e/D ratio from 1.0 to 5.0 with a fixed w/D ratio of 4.0 for CFRP plates, shear and bearing failures occurred together when the e/D ratio exceeded 5.0, suggesting a significantly conservative value compared to the e/D ratio of 2.0 presented in this study.…”
Section: Discussionsupporting
confidence: 92%
“…As the e/D ratio approaches 3.0, both parts of the specimen experience bearing failure, indicating the absence of tension failure (L1I). This result aligns with findings from prior investigations [ 69 , 70 , 71 , 72 , 73 , 74 ]. Alaattin Aktas reported that, while adjusting the e/D ratio from 1.0 to 5.0 with a fixed w/D ratio of 4.0 for CFRP plates, shear and bearing failures occurred together when the e/D ratio exceeded 5.0, suggesting a significantly conservative value compared to the e/D ratio of 2.0 presented in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon was related for two reasons: (1) there was a more extensive transverse section of the rivet to carry the load, and (2) a larger contact area was provided when the rivet diameter increased. McCarthy et al [3,6] reported that variations in the contact area (fastener composites) caused changes in the joint stiffness and ultimate bearing strength. Zhou et al [9] concluded that the geometric parameters (such as the w/D and edge-todiameter (E/D) ratios) should be appropriately chosen.…”
Section: Calculation Of Bearing Strength For Riveted Woven Compositesmentioning
confidence: 99%
“…Mechanical joints for composites, whether by fasteners or rivets, are the only ones that aeronautics authorities have validated regarding the airworthiness certification process [1][2][3]. Riveted composites are currently used in last-generation aircraft, mostly for skin-stringer or skin-beam assemblies in primary structures (e.g., the wing, fuselage and stabilizer) [4] and secondary structures (e.g., flaps, rudder and ailerons) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation